2012
DOI: 10.1142/s0218863512500373
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Instantaneous and Relaxed Kerr Model for Generation of the All-Optical Logic Gates With Triangular Fiber Coupler (Tfc)

Abstract: All-optical logic gates can enable many advanced functions such as all-optical bit-pattern recognition, all-optical bit-error rate monitoring, all-optical packet address and payload separation, all-optical label swapping and all-optical packet drop in optical time domain multiplexing (OTDM) networks. Recently, much attention has been given to the influence of the relaxation process (sometimes called the Debye relaxation model) of the nonlinear response because the usual assumption of instantaneous nonlinear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this work, we aim to obtain all-optical logic gates under the mode on-off keying (OOK) switching using the powerful technology of photonic crystals (PhC's) with the versatility and usefulness of Mach-Zender interferometers (MZI's). This method (on-off keying -OOK) used for obtaining optical contrast level has brought remarkable results in all-optical logic gates field [10,[15][16][17], hence it makes an excellent opportunity for scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we aim to obtain all-optical logic gates under the mode on-off keying (OOK) switching using the powerful technology of photonic crystals (PhC's) with the versatility and usefulness of Mach-Zender interferometers (MZI's). This method (on-off keying -OOK) used for obtaining optical contrast level has brought remarkable results in all-optical logic gates field [10,[15][16][17], hence it makes an excellent opportunity for scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…The light proceeding from ones of the input gates (I1 or I2) will be guided for one of the output gates (O1 or O2), and depend, in linear regime, on the coupling length (Lc). Thus, in the linear regime, the behavior of the coupler is associated to the Lc parameter as [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]:…”
Section: Nonlinear Optical Fiber Couplersmentioning
confidence: 99%
“…Many researchers have addressed general applications with optical logic gates and logic processing signals [6][7][8][9][10][11][12][13][14][15][16][17][18]. The authors in [15] recently demonstrated a new scheme with optical logic operation in a Sagnac interferometer by electro-optical modulation.…”
Section: Introductionmentioning
confidence: 99%